Integrated chemical systems : - Bard, Allen J. (Wiley, 1994)
"Over the past decade, nanotechnology and nanosystems have become subjects of increasing interest, speculation, research, and excitement among chemists, physicists, and engineers concerned with creating a new generation of electronic and biotechnological devices. But most discussion of the process of creating these devices has centered around theoretical systems, and has come from the point of view of potential device-builders such as the electronics industry." "Integrated Chemical Systems is the first book to take a truly systematic approach to the study of nanotechnology, to suggest fruitful avenues of research, and to project in a realistic way the characteristics and applications of future nanosystems. It also provides a firm theoretical basis for the operation of electrochemical and photoelectrochemical nanosystems. These electrochemical methods of surface characterization are extremely promising but have not received the attention already afforded spectroscopy and nuclear magnetic resonance." "Allen J. Bard, noted scientist and leading researcher in the field, begins by discussing and providing numerous examples of actual integrated chemical systems - many of which are taken directly from Professor Bard's own research - and making analogies between man-made systems and those found in nature. Next, Bard moves on to an elementary general treatment of the methods available for the construction and characterization of such systems, followed by a detailed discussion of modified electrodes and electrochemical methods for characterizing them. A full chapter is devoted to semiconductor materials - which may be key components in many systems - and their use in photoelectrochemical systems. The final chapter is devoted to the future of nanotechnology and promising areas for researchers to stake their claims." "For university researchers and students in chemistry, physics, electrical engineering, and materials science, this book provides an elegant introduction to a new field of chemistry and a new batch of concepts that hold enormous potential for future research. Industrial and government researchers concerned with sensors, electronic devices, and electrochemistry will find a host of new principles for device fabrication as well as new ideas for the devices themselves."